Anaemia prevalence and dietary diversity among women in the rural Free State, South Africa - Elizabeth M. Jordaan; Violet L. van den Berg; Francois C. van Rooyen; Corinna M. Walsh (AOSIS, 2020)
Background: Anaemia, a global public health problem that particularly affects women, holds major consequences for human health. Aim: Determining dietary diversity, prevalence of anaemia and contraception use. Setting: Rural women, 25-49 years, in the Free State Province, South Africa. Methods: In a cross-sectional descriptive quantitative study, dietary diversity was determined with a 24-h recall; biochemical markers of anaemia, iron deficiency and inflammation were measured; and contraceptive use was recorded. Results: Of 134 women (median age 41 years), 51.5% had medium, and 44.8% had low dietary diversity. Overall, 76.9% consumed flesh meats and fish, but only 25.4% ate dark green leafy vegetables. Anaemia was present in 4.6%; 1.5% presented with iron deficiency; and 0.7% presented with iron deficiency anaemia, evidenced by low ferritin levels. However, 45.0% had elevated C-reactive protein (CRP). Overall, 7.5% presented with elevated homocysteine levels, but only 3.8% had low red cell folate levels. More than half (54.1%) reported menstruating regularly and 71.6% used injectable contraceptives. Significant associations were found between median mean corpuscular volume (MCV) and mean corpuscular haemoglobin (MCH) and dietary diversity score. Conclusions: Although the prevalence of anaemia is low in this population, elevated CRP in almost half indicates that inflammation may mask iron deficiency. The older median age of the sample and approximately half of the women not menstruating regularly may also contribute to the low anaemia prevalence. Attention should be given to the women's diets as almost half consume diets of low diversity, and not all consume foods rich in haemopoietic nutrients.